Social Identity And Gender Representation of Superheroes And Villains In Indonesia Films - Prihandini, Puji; Zulkifli, Muhammad Yunus (Mediator: Jurnal Komunikasi, 2025)
Indonesian superhero films still adopt Hollywood narratives that imply social identity and gender stereotypes. Previous studies still focus on the main hero characters, while studies that also examine villains are still minimal. This study aims to examine the representation of social and gender identities in Indonesian superhero films by exploring hero and villain characters. This study uses social identity theory and feminist film theory as theoretical foundations. The method used is qualitative with a sociological analysis of two female superhero films, namely: Sri Asih and Virgo and The Sparklings. The data collection method is by observing the narrative, character visualization in the film which is placed in a social and gender context. The results of the study describe the construction of social class between the protagonist and antagonist characters, the dominance of masculinity values ​​and the emphasis on the body and sexuality of the characters. This study concludes that Indonesian superhero films have not depicted inclusive and progressive gender representation. This study contributes to the development of film and gender studies in Indonesia and opens up opportunities for further discussion about popular media